The Level of Physical Fitness of Class V Students of SD Negeri 178 Gegerkalong KPAD Bandung City - Purwanti, Dewi; Slamet, Suherman; Stephani, Mesa Rahmi (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
This research aims to explore the level of physical fitness at SD Negeri 178 Gegerkalong KPAD Bandung City, one of the partner schools of the PGSD Physical Education University of Indonesia. Researchers use purposive sampling, namely students aged 10-12 years consisting of 20 boys and 20 girls in class V. Quantitative descriptive methods were used in this research by describing the data in the form of numbers obtained through the physical fitness test (TKJI). The test components include running 40 meters, hanging bent elbows, lying down for 30 seconds, jumping upright, and running 600 meters. The researchers' findings showed that there were two people in the